Glycosylation of gp41 of Simian Immunodeficiency Virus Shields Epitopes That Can Be Targets for Neutralizing Antibodies - Yuste, Eloìsa (American Society for Microbiology (ASM), 2008)
Human immunodeficiency virus type 1 and simian immunodeficiency virus possess three closely spaced, highly conserved sites for N-linked carbohydrate attachment in the extracellular domain of the transmembrane protein gp41. We infected rhesus monkeys with a variant of cloned SIVmac239 lacking the second and third sites or with a variant strain lacking all three of SIVmac239's glycosylation sites in gp41. For each mutation, asparagine (N) in the canonical N-X-S/T recognition sequence for carbohydrate attachment was changed to the structurally similar glutamine such that two nucleotide changes would be required for a reversion of the mutated codon. By 16 weeks, experimentally infected monkeys made antibodies that neutralized the mutant viruses to high titers. Such antibodies were not observed in monkeys infected with the parental virus. Thus, new specificities were revealed as a result of the carbohydrate attachment mutations, and antibodies of these specificities had neutralizing activity. Unlike monkeys infected with the parental virus, monkeys infected with the mutant viruses made antibodies that reacted with peptides corresponding to the sequences in this region. Furthermore, there was strong selective pressure for the emergence of variant sequences in this region during the course of infection. By analyzing the neutralization profiles of sequence variants, we were able to define three mutations (Q625R, K631N, and Q634H) in the region of the glycosylation site mutations that conferred resistance to neutralization by plasma from the monkeys infected with mutant virus. Based on the reactivity of antibodies to peptides in this region and the colocalization of neutralization escape mutations, we conclude that N-linked carbohydrates in the ectodomain of the transmembrane protein shield underlying epitopes that would otherwise be the direct targets of neutralizing antibodies.